2019
DOI: 10.1038/s41366-018-0315-7
|View full text |Cite
|
Sign up to set email alerts
|

Deletion of translin (Tsn) induces robust adiposity and hepatic steatosis without impairing glucose tolerance

Abstract: Objective: Translin knockout (KO) mice display robust adiposity. Recent studies indicate that translin and its partner protein, trax, regulate the microRNA and ATM kinase signaling pathways, both of which have been implicated in regulating metabolism. In the course of characterizing the metabolic profile of these mice, we found that they display normal glucose tolerance despite their elevated adiposity. Accordingly, we investigated why translin KO mice display this paradoxical phenotype. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
13
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(18 citation statements)
references
References 52 publications
4
13
1
Order By: Relevance
“…In our previous study, we identified several candidate protective factors in Tsn KO mice that may contribute to their ability to retain glucose tolerance [5]. As described previously and as shown in the current study, these mice have a higher proportion of subcutaneous fat, which is thought to protect against glucose intolerance [24].…”
Section: Comparison Of Metabolic Profiles Of Tsnax(e126a) Mice and Tssupporting
confidence: 79%
See 4 more Smart Citations
“…In our previous study, we identified several candidate protective factors in Tsn KO mice that may contribute to their ability to retain glucose tolerance [5]. As described previously and as shown in the current study, these mice have a higher proportion of subcutaneous fat, which is thought to protect against glucose intolerance [24].…”
Section: Comparison Of Metabolic Profiles Of Tsnax(e126a) Mice and Tssupporting
confidence: 79%
“…Following initial characterization of the Tsnax(E126A) mice, we proceeded to compare the metabolic profiles of male and female mice that are homozygous for the Figure 1C) are decreased to a similar extent in both Tsn KO and Tsnax(E126A) mice. We previously showed that the elevated adiposity displayed by Tsn KO mice reflect increases in both visceral and subcutaneous fat depots, with a small but significant preference for subcutaneous fat [5]. Overall, Tsn KO and Tsnax(E126A) mice show very similar increases in both visceral and subcutaneous fat depots.…”
Section: Comparison Of Metabolic Profiles Of Tsnax(e126a) Mice and Tsmentioning
confidence: 78%
See 3 more Smart Citations